Studi Pustaka Phobia Spesifik (Zoophobia) - Putra, Erlangga Anantayudha Nursahid (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
Phobia is an anxiety disorder in which sufferers experience excessive fear of situations, objects and other things. Phobias can be suffered by anyone from gender, age, economy and others. Phobias can be caused by various factors such as experiences, stress or scary events. Phobias can be divided into several things, namely Agrophobia, specific phobias and social phobias. The purpose of this study is to describe the specific phobia. The writing of this research uses the method of library research or library research. In this study, references were collected from journal articles, books, and facts related to a specific phobia (zoophobia). The three references contain the results of the research appointed by the researcher. From these references, an explanation of what phobias and zoophobia are, what causes zoophobia, what types of zoophobia are and how to overcome zoophobia. The result of this study is that the main factor of zoophobia is the experience of the sufferer and frightening events. The anxiety that arises is already in the mind of the sufferer from the beginning of the experience. Therapy and counseling is one of the keys to overcoming zoophobia apart from internal and environmental factors.